2016
DOI: 10.1016/j.clbc.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers That Predict Sensitivity to Heat Shock Protein 90 Inhibitors

Abstract: Purpose HSP90, a viable target for cancer treatment, mediates the maturation and stabilization of client oncoproteins. HSP90i are potentially active in a variety of tumors, but therapeutic benefit is confirmed in only a small subset. We explored potential biomarkers across multiple studies of HSP90i in advanced solid tumors. Methods Archived tumor specimens from patients treated with HSP90i on 7 different phase I/II trials at MSKCC were identified. Tumor tissue was tested by IHC: ER, PR and AR: ≥1% positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Since over- or under-expression of Hsp90 is seen in a variety of tumour types, sometimes in association with gene amplification or loss, and has prognostic impact [ 4 6 , 22 , 23 ], Hsp90 levels could themselves be of predictive value for Hsp90 inhibitor therapy. However, recent data from phase I/II trials of various solid tumour types found that Hsp90 levels are not a predictive biomarker for Hsp90 inhibitor response [ 24 ]. In this respect, the activity of Hsp90 in cancer cells is highly dependent on other chaperones and co-chaperones like AHA1, p23, HOP (also known as STIP1), CHIP (STUB1), Cdc37, Hsp40 and Hsp70 [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since over- or under-expression of Hsp90 is seen in a variety of tumour types, sometimes in association with gene amplification or loss, and has prognostic impact [ 4 6 , 22 , 23 ], Hsp90 levels could themselves be of predictive value for Hsp90 inhibitor therapy. However, recent data from phase I/II trials of various solid tumour types found that Hsp90 levels are not a predictive biomarker for Hsp90 inhibitor response [ 24 ]. In this respect, the activity of Hsp90 in cancer cells is highly dependent on other chaperones and co-chaperones like AHA1, p23, HOP (also known as STIP1), CHIP (STUB1), Cdc37, Hsp40 and Hsp70 [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, it is clear that some patients benefit, whilst others do not, a problem exemplified by our demonstration of plateau effects in some cell lines–patients with these types of tumours are unlikely to show any benefit. Thus, there is a need for predictive biomarkers, but the only strong indicator of response in a series of Phase I/II trials appears to be ErbB2 [ 24 ], whereas other markers including Hsp90, Hsp70, EGFR and steroid receptors were not predictive. This contrasts with the observations that triple-negative breast cancers (that lack ErbB2) may show a good response to Hsp90 inhibitors [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our group conducted a retrospective study to explore potential biomarkers in patients treated with HSP90 inhibitors. Among many potential candidates analyzed (HER2, HSP90, HSP70, phosphotension homolog), HER2 was found to be the most important individual biomarker and the only one with correlation to response with HSP90 inhibitor therapy [ 44 ]. While tumor biopsies have been undertaken in some trials and can serve as a useful tool to establish target modulation, they provide only static information for a small part of the tumor and cannot account for the heterogeneity of metastatic tumor burden.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the only reliable way to predict response to HSP90 inhibition has been to identify those patients whose cancer is driven by a particular oncogene that is a very sensitive HSP90 client (e.g., HER2 in breast cancer or chimeric ALK in NSCLC) [97]. Nonetheless, clinical success in other tumor types that harbor HSP90 onco-clients has been limited so far and the failure of HSP90 inhibitors in these tumors remains poorly understood.…”
Section: Biomarkers and Diagnostics – Unmet Need In Hsp90 Therapymentioning
confidence: 99%